Can pharmacogenetics explain efficacy and safety of cisplatin pharmacotherapy? - Roco, Ángela; Cayún, Juan; Contreras, Stephania; Stojanova, Jana; Quiñones, Luis (Frontiers in Genetics, 2014)
In recent times, several investigations have been seeking an explanation for the great variability in both outcome and toxicity in cisplatin-based therapy through pharmacogenetic studies. These studies have focused on the genetic variability of therapeutic targets that could affect cisplatin response and toxicity in diverse type of cancer including lung, gastric, ovarian, testicular and esophageal cancer. In this review, we seek to update the reader in this area of investigation, focusing primarily on DNA reparation enzymes and cisplatin metabolism through Glutathione S-Transferases (GST) genes. Current evidence indicates a potential application of pharmacogenetics in therapeutic schemes where cisplatin is the cornerstone of these treatments. Therefore, a collaborative effort is required to study these molecular characteristics in order to generate a genetic panel with clinic utility.